MEMPOSISIKAN BALI SEBAGAI DAERAH TUJUAN WISATA DI ANTARA PESAINGNYA - Tarunajaya, Wisnu Bawa (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2010)
This research aims to find out the competitiveness of Bali as a tourism destination among its competitors: Malaysia, Thailand, and Singapore. A number of I 3 attributes which are considered by tourists in choosing a destination was developed into a questionnaire to position Bali among the above competitors. The collected data (J 04 questionnaires) were analyzed by using Multi-Dimensional Scaling (MDS). The research found out that the hospitality of local people, culture, history, and beach obtain high scores. Cleanliness was scored the lowest so that this problem needs very serious attention.